2015
DOI: 10.1007/s10461-014-0987-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Recruiting Peer Educators to Promote HIV Testing Using Facebook Among Men Who have Sex with Men in Peru

Abstract: A peer leader-based intervention using social media can be an effective means to encourage Peruvian gay men to test for HIV. The objective was to explore the feasibility of recruiting and training leaders to deliver a peer intervention via Facebook to promote HIV testing. Training consisted of three sessions focused on HIV epidemiology, consequences of stigma associated with HIV, and ways to use Facebook. We performed pre- and post-training evaluations to assess HIV knowledge and comfort using Facebook. We tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…1 ). Forty-one of these 51 publications corresponded to unique studies; in addition, three publications belonged to Project HOPE ( 26 , 40 , 43 ); three were part of the Get Yourself Tested campaign ( 19 , 37 , 50 ); two papers referred to the FaceSpace Project ( 23 , 33 ); and two studies reported on an HIV self-test campaign on Grindr. All the included studies were carried out between 2008 and 2015.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Forty-one of these 51 publications corresponded to unique studies; in addition, three publications belonged to Project HOPE ( 26 , 40 , 43 ); three were part of the Get Yourself Tested campaign ( 19 , 37 , 50 ); two papers referred to the FaceSpace Project ( 23 , 33 ); and two studies reported on an HIV self-test campaign on Grindr. All the included studies were carried out between 2008 and 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen of them only showed data regarding project reach and engagement (number of users, time spent, etc.) ( 23 , 28 , 30 , 43 , 48 , 54 , 56 , 59 – 69 ), while another 10 publications additionally showed data on STI incidence and testing ( 19 , 24 , 36 , 37 , 47 , 49 , 51 – 53 , 55 ). The designs in 12 of the publications combined quantitative data on technology use and also questionnaires or opinions of project users regarding their satisfaction, knowledge, engagement, or behavior change (intention to test) ( 29 , 30 , 33 , 34 , 39 , 41 , 42 , 46 , 50 , 58 , 63 , 67 ).…”
Section: Resultsmentioning
confidence: 99%
“…5622 Ageism and broken connections between generations result in missed opportunities for important community connectedness and peer support, 42628 as mentorship relationships between older and younger GBM often have positive social- and community-level benefits beyond sexual relationship satisfaction. 3334 Furthermore, our finding regarding increased odds of intergenerational partnerships among Asian and Latino GBM in Vancouver has important implications, and highlight a need for increased sexual health promotion messaging and further research examining sexual relationships and behaviour partners among racial and ethnical minorities of GBM. It is imperative that interventions and community initiatives aim to combat deeply entrenched age- and HIV- related stigma through the promotion of positive and safe sexual relationships between GBM of all ages, ethnicities, regardless of HIV status.…”
Section: Discussionmentioning
confidence: 87%
“…[36,11,15] Both opt-out models at STI clinics and social media innovations that normalize and promote frequent testing could prove beneficial in reaching these higher risk groups. [35,36] …”
Section: Discussionmentioning
confidence: 99%